Romanticism In Madurese Song Lyrics On Fajar Syahid’s Youtube Channel - Dela Febriyanti; Dzarna Dzarna; Dina Merdeka Citraningrum (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2025)
This study aims to describe the most dominant characteristics of romanticism in a collection of Madurese song lyrics uploaded to Fajar Syahid's YouTube channel. This study was motivated by the limited research on the aesthetic and emotional values in regional songs, especially Madurese songs. The focus of the study is on the three most dominant characteristics of romanticism, namely melancholy or gloom, sentimentality, and individualism. The method used is qualitative descriptive with a romanticism approach. The data sources were 15 Madurese song lyrics selected through a reduction technique and categorized based on six characteristics of romanticism, namely return to nature, gloom or melancholy, primitivism, sentimentality, individualism, and exoticism. The analysis was carried out by identifying, interpreting, and describing lyrics that reflect the characteristics of romanticism. The results of the study show 42 instances of romanticism, including melancholy (14), sentimentality (15), individualism (7), return to nature (1), exoticism (2), and primitivism (3). These findings show that the most dominant characteristics are melancholy, sentimentality, and individualism. Melancholy is depicted through expressions of deep sadness and loss; sentimentality through outbursts of love and excessive longing; and individualism through characters who tend to be reclusive and bottle up their feelings. The results of the study confirm that Madurese song lyrics not only serve as entertainment, but also represent literary value and emotional depth that are relevant to be studied as part of the local literary heritage based on regional culture.